Effect Type Of Packaging Material And Storage Time On Total Plate Count (Tpc) Microbes On Shrimp Paste Chili Sauce - Bari, Agata j i (Department of Biology Education, Faculty of Teacher Training and Education, Universitas Wijaya Kusuma Surabaya, 2024)
This research aims to determine the effect type of packaging material and storage time on microbial Total Plate Count on the shrimp paste chili sauce, a completely randomized design (RAL) of two factorial was used in this research. The first factor was the type of storage material consisting of plastic bottles (A1) and glass bottles (A2). The second factor was the length of storage consisting of 5 days (H1), 10 days (H2) and 15 days (H3). From the two factors, 6 combinations of treatments were obtained, and each treatment combination was repeated 4 times, so the total was 24 samples. The results of the research were analyzed using variance at a realistic level of 5%, if significantly different then continued with the Duncan test. The results showed that the type of packaging and storage time had a significantly different effect on the parameters of the microbial Total Plate Count on the shrimp paste chili sauce (p<0.05). Based on the results, it is known that the use of glass bottle packaging (A2) has a better ability to maintain the quality of shrimp paste sauce. Referring to the SNI standard (01 - 7388 - 2009), the best storage time for shrimp paste sauce is 10 days (H2), with an average microbial Total Plate count that is still within the normal range of 4.0 x 104 CFU/g < 1 x 105 CFU/g. The implication of this research is that the use of glass bottle packaging materials is able to maintain the quality of shrimp paste sauce better than plastic bottles and the best storage time for the shrimp chili paste is 10 days.